Correlations between Central Corneal Power, Axial Length, Anterior Chamber Depth and Central Corneal Thickness of near-Emmetropic Young University Students in Palestine - Aljarousha, Mohammed; Abo Daqa, Ansam; Qanan, Fatma; Murtaja, Haya; Baraka, Nadeen (Jordan Medical Journal, 2021)
Purpose: To investigate the correlation between the central corneal power (CCP) and a panel of variables which include axial length (AL), axial depth of the anterior chamber (ACD), and the central corneal thickness (CCT) in emmetropic eyes in young students in the Optometry Lab of the Islamic University-Gaza (IUG), Palestine. Methods: In a prospective analysis, 200 emmetropic students were examined from February to May 2019 by the Ultrasound Scanner (A-scan), Ultrasonic Pachymeter, and Visionix L79 Automated Refractometer Keratometer (ARK)-Topography machines. Only the data of one eye was randomly chosen for investigation. The age range was 18-23 years with spherical equivalent (SE) refractive error of less than ± 0.50 D. Results: The means and standard deviations (SD) of the CCP, AL, ACD, and CCT of the near-emmetropic male students (n=97) were 43.19 ± 1.34 D, 23.54 ± 0.68 mm, 3.59 ± 0.26 mm, and 549 ± 33 µm , respectively. In addition, the means ± SD in female subjects in 103 near-emmetropic female students of CCP were 43.85 ± 1.43 D, AL 22.94 ± 0.69 mm, ACD 3.35 ± 0.25 mm, and CCT 543 ± 35 µm. There was a significant association between CCP and gender (p=0.00). However, there was no significant difference in CCP values between the age groups (p=0.49). There was a negative significant correlation between CCP and AL for both the males (r=-0.64; p=0.00) and the females (r=-0.71, p=0.00) participants. The values of the correlation (r) were 0.15 and 0.08 between CCP and ACD of the male and female participants respectively. Additionally, no significant correlation was found between CCP and CCT for male and female eyes (p=0.16, p=0.86, respectively). Conclusion: This study provided information for CCP, AL, ACD, and CCT in near-emmetropic eyes in young students in the optometry lab at the IUG, Palestine. Scores of CCP was normally distributed. CCP was not significantly influenced by age, ACD and CCT. In male students CCP was flatter, and AL was longer when compared with female Palestinian young students